2020
DOI: 10.3390/en13246626
|View full text |Cite
|
Sign up to set email alerts
|

Technological Effectiveness of Sugar-Industry Effluent Methane Fermentation in a Fluidized Active Filling Reactor (FAF-R)

Abstract: Technological solutions allowing the increase of the technological efficiency of anaerobic methods of wastewater treatment are still under investigation. The weaknesses of these solutions can be limited by the use of active fillings. The aim of the present study was to determine the impact of fluidized active filling on the effectiveness of anaerobic treatment of sugar-industry effluent, the production efficiency and the qualitative composition of the biogas produced. High, comparable (p = 0.05) effluent treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…In recent studies, it was proved that the magnetic field exerts a positive effect on many properties of fluids, i.e., it changes the polarization, and electric charge decreases surface tension and increases viscosity. In studies conducted so far, the magnetic field has usually been applied to separate solids, like, e.g., activated sludge, from the effluent [33,34]. It was also demonstrated to influence the growth and metabolism of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, it was proved that the magnetic field exerts a positive effect on many properties of fluids, i.e., it changes the polarization, and electric charge decreases surface tension and increases viscosity. In studies conducted so far, the magnetic field has usually been applied to separate solids, like, e.g., activated sludge, from the effluent [33,34]. It was also demonstrated to influence the growth and metabolism of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The l demonstrate that its presence in the start-up phase favors the form microbial granules from the flocculant. Not only was their hypothesis c solid retention was also independent of the hydrodynamic conditions i This means that this solution can be applied to both UASB and EGSB r et al [52] tried to overcome the limitations of the anaerobic treatment means of the innovative solution of the fluidized active filling reacto their experiment, the effect of FAF on sugar industry effluent was t organic loading rates (OLR), more precisely from 4 to 6 kgCOD/m 3 d. T that, within this OLR range, the COD removal efficiency was greater methane yield was greater than 70%. However, when the OLR was kgCOD/m 3 d, the effluent treatment efficiency strongly decreased mai An innovative solution was proposed by Torres et al [51], who carried out several experimental tests on laboratory scale reactors seeded with sludge coming from wastewater treatment plants (WWTPs) located in Spain.…”
Section: Sludge Bed Reactormentioning
confidence: 96%
“…This means that this solution can be applied to both UASB and EGSB reactors. Debowski et al [52] tried to overcome the limitations of the anaerobic treatment of wastewater by means of the innovative solution of the fluidized active filling reactor (FAF-R). During their experiment, the effect of FAF on sugar industry effluent was tested at different organic loading rates (OLR), more precisely from 4 to 6 kgCOD/m 3 d. The results showed that, within this OLR range, the COD removal efficiency was greater than 74% and the methane yield was greater than 70%.…”
Section: Sludge Bed Reactormentioning
confidence: 99%
“…The optimization carried out has shown that the theoretical optimum operating conditions (922 mg/L SO 4 2− , ISR = 3.72) are expected to generate 361 mL biogas/gVS, 235 mL CH 4 /gVS, with reduction efficiencies of 27.5% VS, 27.4% TS, 75.1% TOC, 75.6% SO 4 2− , and 41.1% COD [1]. Dębowski and Zielinski [2] conducted research to determine the impact of fluidized active filling on the effectiveness of the anaerobic treatment of sugar-industry effluent and the production efficiency and qualitative composition of the biogas produced. The research was carried out on a fractional-technical scale.…”
Section: Wastewater Treatment Technologiesmentioning
confidence: 99%